A Study of the Geological & Geo – Engineering Environments to Balouta Dam in Tartous - عروس سارة; محمد عبدالله عيسى (Latakia University Journal -Basic Sciences Series, 2024)
The research shows the lithological and geo – engineering properties of the dam axis and the penetration along this axis, and the dam lake. The research also localizes the geological units, which differ in its geo – engineering properties, during rocks cors study and surface samples therefore have shaped non- penetrating, thus, these units were classified according to their influence in two basic ranges: Penetrating strip on the right shoulder of the dam, the thickness is 5 m and at depth 10 m, thickness decreases in the direction of the dam axis. Under this strip there is un-penetrating dolomite marl limestone. Moreover, as a result of the study of the physical and lithological properties of the rocks forming the dam shoulders, don’t allow large water loss.